Analisis Pandangan Abdul Moqsith Ghazali dan Hamid Fahmy Zarkasyi terhadap Pluralisme Agama dalam Penafsiran Ayat-Ayat Al-Quran - Fauzan Hidayatullah (Program Studi Aqidah dan Filsafat Islam, 2023)
The issue of religious pluralism continues to resonate in the millennial era. In this context, Abdul Moqsith Ghazali and Hamid Fahmy Zarkasyi are two contemporary figures whose perspectives and interpretations of Quranic verses related to religious pluralism are relevant for further examination. The aim of this research is to analyze the views of both figures on religious pluralism and their interpretations of verses regarding the salvation of religious communities found in Surah Al-Baqarah [2]:62 and Surah Al-Maidah [5]:69. This study employs a library research method, utilizing primary data from Abdul Moqsith Ghazali's work,